FREE CASH FLOW, STRUKTUR KEPEMILIKAN, DAN STRUKTUR MODAL : Dampak Terhadap Agency Cost di Indonesia - Yoga Khomaini Aditya (2020)
The study was conducted to determine the effect of free cash flow, managerial ownership, outsider block ownership, and capital structure on agency costs in Indonesia. The population in this study is non-financial sector companies that have been listed on the Indonesia Stock Exchange from 2014 to 2018. Purposive sampling technique is a sampling technique in this study so that there are 100 companies with 5 years of observation. Analysis techniques using the IBM SPSS version 25 application with a significance level of 5%. The independent variable influencing the dependent variable in this study was shown at 23.2% while the remaining 76.8% was influenced by other factors. The results of this study explain that free cash flow, managerial ownership, capital structure have a significant positive effect on agency cost. Meanwhile, outsider block ownership does not affect on agency cost.